INTER-RELIGIOUS DIALOGUE IN ASIA- I - Thottakara, Augustine (Journal of Dharma, 2000)
For the past twenty-five years we have brought out Journal of Dharma without any interruption. We were able to send you four issues a year from 1975. Of course, all issues were not equally good or perfect. We are also aware that we could not dispatch to you some of the issues in the stipulated time. Still it is with great satisfaction and feeling of fulfillment that we look back to the past history of Journal of Dharma.